Four-Day Workweek in Indonesia’s Big Cities: Urgency and Legal Framework for Flexible Work in Labour Law Reform - Shinta Ks; Fredsly Hendra Sardol Girsang; Khairina Widiyanti; Sugeng Santoso Santoso (Jurnal Ketenagakerjaan, 2026)
This article offers normative input for Indonesia’s ongoing labour-law reform agenda by proposing a legal framework to govern a four-day workweek as part of broader flexible-work regulation. Indonesian working-time norms remain largely anchored in a 40-hour standard, while contemporary work arrangements, particularly hybrid (hibrida) and remote (jarak jauh) work, have heightened risks of working-time spillover, hidden overtime, and blurred boundaries between work and rest. Within this reform context, the study assesses the legal urgency and basis for regulating a four-day workweek and formulates a fair and safe implementation model through a proposal to establish a Flexible Work Chapter within a revised/new Labour Law and its implementing regulations. Using a normative-prescriptive legal method, the research applies statutory, conceptual, and comparative approaches, supported by desk-based evidence from published evaluations of four-day workweek trials in the UK and Iceland and scholarship on the European right to disconnect. The findings indicate that a four-day workweek may be operationalized through two legal models, compressed workweeks (40 hours/4 days) and reduced-hour workweeks (32–36 hours/4 days), each carrying distinct legal implications and risks, particularly in sectors and urban contexts where working-time control is difficult. Accordingly, safeguards are required, including wage protection, clear overtime limits and approval, transparent working-time recording (including for hybrid/remote arrangements), strengthened Occupational Safety and Health (OSH) and fatigue-risk management, and a right to disconnect framework. The article concludes that a Flexible Work Chapter is necessary to ensure flexibility remains consistent with worker-protection principles and legal certainty in working-time governance.